A transition in the electrical conduction mechanism of CuO/CuFe2O4 nanocomposites - Ozdemir, Zeynep Guven; Kilic, Mehmet; Karabul, Yasar; Misirlioglu, Banu Sungu; Cakir, Oznur; Kahya, Naime Didem (SPRINGER, 2020)
The complex impedance, complex permittivity and, alternating current (ac) conductivity investigations of the CuO/CuFe2O4 nanocomposites, prepared by using via co-precipitation and sol-gel methods, were performed between 1 Hz and 40 MHz within 296 K-433 K in the present study. The structural analyses of the samples were determined by scanning electron microscope (SEM), X-ray diffraction (XRD) analysis, energy dispersive X-ray (EDX) spectroscopy and X-Ray Fluorescence (XRF) techniques. The ac impedance and complex permittivity results revealed that these ferrite systems have a heterogeneous structure consisting of conducting grains surrounded with less conducting grain boundaries which are expressed by Koop's model. Additionally, the temperature dependent dc conductivity showed up the semiconductor-conductor and conductor-semiconductor transitions in different temperatures. From this point of view, the nanocomposites exhibiting conductive or semiconductor behavior depending on temperature have the potential to be used in many electronic devices, including sensor applications. Moreover, the activation energies of the samples calculated by the Arrhenius plots of the dc conductivity indicated both electron and hole hopping processes for the conduction. Furthermore, small polaron charge transport mechanism was implied by the high activation energies. Ac conductivity analyses of the samples showed that the ferrites prepared in the present work exhibit correlated barrier hopping dominantly for the ac conduction. Graphical
Keywords: Copper ferrite; Semiconductor-metal-semiconductor transition; Nanocomposite; Ac conductivity; CBH model; MAGNETIC-PROPERTIES; FERRITE NANOPARTICLES; DIELECTRIC-PROPERTIES; TEMPERATURE-DEPENDENCE; IMPEDANCE; COMPOSITE; BEHAVIOR; OXIDE; ENHANCEMENT; Materials Science